Men's awareness of cervical cancer: a qualitative study - Hae Won Kim; Duck Hee Kim; Youngji Kim (BMC, 2018)
Abstract Backgrounds As HPV is a sexually transmitted virus, men are crucial in the prevention of cervical cancer, but research about men's awareness on cervical cancer is limited. Therefore, in this study, we investigated men's awareness toward women's cervical cancer, to thoroughly understand the viewpoints of men, and to emphasize the centrality of the role of men in the prevention of cervical cancer. Methods A qualitative descriptive design was chosen to explore men's awareness of women's cervical cancer. Twelve men aged 20-58 were interviewed. Snowball sampling was conducted to recruit participants. Results Most participants stated that they were not interested in women's health, and that they did not have much knowledge about cause and prevention of cervical cancer. They acknowledged that cervical cancer was different from other cancers, based on cause and prognosis of disease. The recognition of cervical cancer in participants varied widely depending on their relationship with women. Respondents' recognition of cervical cancer was classified into four types based on a Situational Awareness (SA) model including individual factors (knowledge about cervical cancer, interest in women's health) and system/task factors (relationship with women, men's responsibility). Conclusion This study is one of the few studies describing men's awareness on cervical cancer. Korean men's awareness level was low, and their concern and knowledge were not good. Some participants thought that cervical cancer can be treated, can be prevented, and is recognized as a disease of a female with men intervening. Our participants perceived that the role of men is necessary for the prevention of cervical cancer. Therefore, a strategy is needed to develop the awareness and knowledge of men on cervical cancer prevention. When planning cervical cancer education for men, phase and type-specific approaches are required, depending on perception level.